Financiamento da seguridade social: análise do entendimento do STF sobre a exclusão do ICMS da base de cálculo do PIS/COFINS – recurso extraordinário nº 574.706/PR - Lopes, Hélio Benigno (Universidade Federal Rural do Semi-Árido, 2017)
The Social Security Financial Contributions (COFINS) and contributions to Social Integration Programs (PIS) are two of the main sources of social security financing. The objectives of this article are to identify the impact of the Federal Supreme Court's (STF) agreement on social security financing with the exclusion of the Tax on the Circulation of Goods and Services (ICMS) from the PIS/COFINS calculation basis; To point out the conceptual and historical aspects of social security; Highlight the importance of PIS/COFINS for social security funding/financing; In addition, to analyze the STF's understanding of the exclusion of ICMS from the PIS and COFINS calculation base. 4 The methodology used was the exploratory research, through a bibliographical survey in books, dissertations, articles, legislation and consultation on the Internet. An analysis of the judgment regarding RE 574.706/PR was also carried out, which is processed in the STF with general acknowledged repercussions. The decision of the STF should have its effects modulated ex nunc, failing to favor only taxpayers, since according to their claims that they are only collectors of the State, they would not return to the real taxpayers who paid the ICMS included in the costs of the goods and or services Purchased. It was verified that the non-modulation of the effects of the decision to exclude the ICMS from the PIS and COFINS calculation basis may have a negative impact on the Social Security budget by more than R$ 200,000,000,000.00 (two hundred billion reais).
Artigo Acadêmico
Keywords: Seguridade social; PIS/COFINS; RE 574.706/PR; STF; Social Security; CIENCIAS SOCIAIS APLICADAS::DIREITO